Faktor-Faktor Yang Berhubungan dengan Motivasi Petani Menanam Mangrove Di Desa Mayangan Kecamatan Gumukmas Kabupaten Jember, Jawa Timur - Ridlo Wahyudi; Lenny Widjayanthi; Sri Subekti (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
The purpose of this research is to find out factors related to farmer's motivation to grow mangrove in Mayangan Village, Gumukmas Sub-district, Jember District. The method used in this study uses descriptive and correlational methods. The result of the analysis shows that the variables of experience, formal education and non-formal education have a relationship with the motivation of farmers to plant mangrove while other variables such as age and number of family members have no relationship, at 95% confidence level.